2019
DOI: 10.1186/s12887-019-1598-0
|View full text |Cite
|
Sign up to set email alerts
|

Deep coma in a child treated with propranolol for infantile hemangioma

Abstract: Background Propranolol hydrochloride is the first-line agent recommended for the treatment of infantile hemangiomas (IH). Serious adverse effects of propranolol therapy for hemangiomas are infrequent. Case presentation We report a case presented in deep hypoglycemic coma during his treatment with propranolol for IH. Through our case report and the review of the literature, we aimed to underline the importance of recognizing adverse effects during propranolol therapy. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…We are aware of an infant in our own institution who required cardiopulmonary resuscitation during an episode of bronchial disease while on oral propranolol treatment. Other reports of severe adverse reactions to propranolol include hypoglycaemic coma and fatal hyperkalaemia during general anaesthesia [15,16]. Therefore, it is recommended that infants on systemic propranolol are closely monitored and that parents are counselled to discontinue propanolol during times of poor feeding and respiratory illness and to make the anaesthetist aware of the propanolol treatment [4].…”
Section: Discussionmentioning
confidence: 99%
“…We are aware of an infant in our own institution who required cardiopulmonary resuscitation during an episode of bronchial disease while on oral propranolol treatment. Other reports of severe adverse reactions to propranolol include hypoglycaemic coma and fatal hyperkalaemia during general anaesthesia [15,16]. Therefore, it is recommended that infants on systemic propranolol are closely monitored and that parents are counselled to discontinue propanolol during times of poor feeding and respiratory illness and to make the anaesthetist aware of the propanolol treatment [4].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, some dermatologists remain reluctant to use propranolol due to potential serious adverse effects in young patients. 7 Studies revealed that the efficacy rate of propranolol was greater than that of corticosteroids in treating IH. Additionally, propranolol had fewer complications than steroids.…”
Section: Discussionmentioning
confidence: 99%
“…Six of 35 infants (17.1%) who were treated with oral propranolol underwent retinopathy of prematurity intervention, as opposed to 14 of 36 (38.9%) control infants [21]. An 18 month old boy presented caries in the upper central incisors following the use of propranolol solution for the treatment of an infantile haemangioma [22].…”
Section: Adverse-effects Caused By Propranolol In Infants and Childrenmentioning
confidence: 99%